Cost Accounting on the CPA Examination. - Usry, Milton F. (The Accounting Review, 1966)
The article analyzes the extent and types of coverage of cost accounting topics during the Uniform Certified Public Accountant Examination in the U.S. from 1956 to 1965. Although the cost content has fluctuated considerably from one examination to another, the significance of the composite time percentages of 25 percent of the practice and 15 percent of the theory examination devoted to cost denotes the importance of the area. The author concludes that shifts in emphasis are usually fairly gradual and the major topics suggested in this paper should offer guidelines for preparation in the immediate future and until other trends become noticeable.